Information and Communication Crime - Metenko, Jozef (Communications - Scientific letters of the University of Zilina, 2005)
In this paper the author tries to shortly characterize the content and scope of crime connected with information and communication technologies. He analyses the (known) possibilities to commit crime connected with abuse of information and communication systems. These are registered in the uncovering and clarifying activities performed by police officers. He demonstrates ground conditions under which such crime arise, as well as their specialities. The author points out some possibilities within the crime control, as a practical analysis on the basis of police sciences, law, criminology and criminalistics.